2020
DOI: 10.1257/jep.34.3.128
|View full text |Cite
|
Sign up to set email alerts
|

Place-Based Policies and Spatial Disparities across European Cities

Abstract: Spatial disparities in income levels and worklessness in the European Union are profound, persistent and may be widening. We describe disparities across metropolitan regions and discuss theories and empirical evidence that help us understand what causes these disparities. Increases in the productivity benefits of cities, the clustering of highly educated workers and increases in their wage premium all play a role. Europe has a long-standing tradition of using capital subsidies, enterprise zones, transport inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(35 citation statements)
references
References 48 publications
1
33
0
1
Order By: Relevance
“…Their impacts have often been limited and not sustainable. Sometimes, they largely amount to beggar-thy-neighbor policies that shift activity and employment from one place to another (Ehrlich and Overman 2020). That said, infrastructure policies seem to work better than tax exemptions, or employment and investment subsidies.…”
Section: A Spatially Blind Spatially Connective and Spatially Targmentioning
confidence: 99%
“…Their impacts have often been limited and not sustainable. Sometimes, they largely amount to beggar-thy-neighbor policies that shift activity and employment from one place to another (Ehrlich and Overman 2020). That said, infrastructure policies seem to work better than tax exemptions, or employment and investment subsidies.…”
Section: A Spatially Blind Spatially Connective and Spatially Targmentioning
confidence: 99%
“…It shows that (a) regional mobility frictions are higher than sectoral mobility frictions and (b) a crisis that is initially transmitted through one sector quickly spreads to other sectors. (For instance, estimates in the United States and the European Union suggest that a job in a tradable sector creates between 0.5 and 1.5 extra jobs in nontradable sectors [Ehrlich and Overman 2020]; thus, the loss of a tradable job might lead to additional job destruction in downstream or upstream sectors.) The most affected workers will be difficult to identify, because they are likely to work in sectors not initially affected by the shock.…”
Section: Beyond Short-term Income Support: Policy Actions To Get People Back To Work and Reskill Themmentioning
confidence: 99%
“…In other words, the reduction of mobility costs across regions would do more to mitigate a crisis-induced welfare reduction Local job creation efforts often involve (a) investments in infrastructure and in local public goods and services, (b) direct subsidies to firms, or (c) the relocation of public sector employment or large public agencies to depressed areas. Neumark and Simpson (2015) provide an overview of the literature on these types of policies, updated by Ehrlich and Overman (2020) in the context of the European Union (EU). Overall, the evidence suggests that investment in transportation infrastructure and in local public goods and services in a mix of firm subsidies and training, as is done by the EU's cohesion funds, has on average been effective at fostering growth in recipient localities and thus at reducing disparities across places in economic opportunities (Becker, Egger, and Ehrlich 2010;Giua 2017;Mohl and Hagen 2010;Pellegrini et al 2013).…”
Section: Addressing the Spatial Dimension Of Crises' Impacts On Workersmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the many failures to revive urban economies outside the major population centers, many economists have concluded that the agglomeration effects of large cities may have become a major cause for growing regional disparities and social inequality, resulting in an increasing gap between rural and urban regions [75,76].…”
Section: Transactions Of Decline Versus Economic Revival Through Entrepreneurshipmentioning
confidence: 99%